Search for decays of B-0 mesons into pairs of leptons: B-0 -> e(+)e(-), B-0 ->mu(+)mu(-), and B-0 -> e(+/-)mu(-/+) - Bergfeld, T; Eisenstein, B; Ernst, J; Gladding, G; Gollin, G; Hans, R; Johnson, E; Karliner, I; Marsh, M; Palmer, M; Plager, C; Sedlack, C; et al. (2000)
We search for the decay of the B0 meson into a pair of leptons in the suppressed channels B0→e+e-, B0→μ+μ- and in the lepton number violating channel B0→e±μ∓ in a sample of 9.7×106 BB̄ pairs recorded by CLEO detector. No signal is found, and the following upper limits on the branching fractions are established: B(B0→e+e-)<8.3×10-7, B(B0→μ+μ-)<6.1×10 -7, B(B0→e±μ ∓)<15×10-7 at 90% confidence level. A new lower limit on the Pati-Salam leptoquark mass MLQ>27 TeV is established at 90% confidence level. © 2000 The American Physical Society.